THE INFLUENCE OF PICTURE AND PICTURE TYPE COOPERATIVE LEARNING MODELS ON IPS LEARNING OUTCOMES - Murtado; Tetep; Eldi Mulyana (Institut Pendidikan Indonesia, 2023)
We can know the learning model from various sources as material for teaching and learning activities, in fact, the learning model exists to help teachers in the teaching and learning process so that it can be conveyed to students better and not saturated when the teaching and learning process takes place. Picture and picture type cooperative learning model as one of the learning models that can be used in the process of teaching and learning activities, where this model uses pictures as teaching media, but in fact, social studies educators, especially at SMP Negeri 2 Leles, rarely use other learner models and only use conventional models as learning models in the process of teaching and learning activities so that students tend to get bored, making many students' learning outcomes still under KKM. To determine the effect of learning using this picture and picture type cooperative learning model, researchers use a quantitative approach with a type of quasi-experimental research. The subjects of the study were class VIII SMP Negeri 2 Lelesa with class VIIIA as the experimental class and class VIIIB as the control class. The results showed differences in student learning outcomes before and after using the picture and picture type cooperative learning model in the teaching and learning process, this can be seen from the post-test scores that exceed the pre-test scores, this shows that students better understand social studies learning material when using learning models in the teaching and learning process, meaning that the picture and picture type cooperative learning model has a good influence on social studies learning outcomes where students experience improved learning outcomes.